Spatial Dependence of OCT-Based Measurements of Stratum Corneum Thickness and External Ridge Width on Human Digital Core - Neves, Macsiel Nunes Lima; da Cruz Júnior, Luismar Barbosa; Pratavieira, Sebastião; Garcia, Marlon Rodrigues [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2025)
This pilot study investigates whether the position of Optical Coherence Tomography (OCT) measurements affects the thickness of the stratum corneum (SC) and the width of external ridges (ER) at the center of the digital. OCT images were acquired from six healthy male volunteers at four fingertip positions. Statistical analysis revealed no significant differences in SC or ER measurements across positions. These findings suggest that OCT provides stable and position-independent assessments within the digital core region, supporting its use in dermatological and biometric applications, and guiding future clinical studies involving skin microstructure analysis.